2019
DOI: 10.1186/s12967-019-1876-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of MAML1 in targeted therapy against the esophageal cancer stem cells

Abstract: Background Esophageal cancer is the sixth-leading cause of cancer-related deaths worldwide. Cancer stem cells (CSCs) are the main reason for tumor relapse in esophageal squamous cell carcinoma (ESCC). The NOTCH pathway is important in preservation of CSCs, therefore it is possible to target such cells by targeting MAML1 as the main component of the NOTCH transcription machinery. Methods In present study we isolated the CD44+ ESCC CSCs and designed a MAML1-targeted thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…As a potential cancer therapeutic agent, GO could effectively inhibit the migration and invasion of human breast and prostate cancer cells and mouse melanoma cells [25]. The cancer stem cells were responsible for tumor relapse and treatment resistance, and became the focus of tumor therapy [26,27]. In this study, we demonstrated that GO could inhibit the growth and formation of GSC spheres and reduce their malignant properties by inducing the differentiation of GSCs.…”
Section: Discussionmentioning
confidence: 77%
“…As a potential cancer therapeutic agent, GO could effectively inhibit the migration and invasion of human breast and prostate cancer cells and mouse melanoma cells [25]. The cancer stem cells were responsible for tumor relapse and treatment resistance, and became the focus of tumor therapy [26,27]. In this study, we demonstrated that GO could inhibit the growth and formation of GSC spheres and reduce their malignant properties by inducing the differentiation of GSCs.…”
Section: Discussionmentioning
confidence: 77%
“…The Notch signaling pathway plays an important role in regulating cell differentiation and proliferation during embryogenesis and normal tissue homeostasis, which have also been implicated in tumorigenesis including development of esophageal cancer [ 125 ]. Mastermind like1 (MAML1) is a key transcription coactivator of this pathway, which could promote the aggressiveness of ESCC through an upregulation of the EMT marker TWIST1 and increase the therapy resistance of ESCC stem cells, respectively [ 126 , 127 ]. In addition, Notch signaling is frequently activated in poorly differentiated tumors and drives a CSC phenotype.…”
Section: Ecsc Signaling Pathwaysmentioning
confidence: 99%
“…NOTCH signaling pathway has a pivotal role in various cellular processes such as cell cycle, migration, metabolism, and apoptosis [150,151]. MiR-129-5p is involved in tumor cells drug response via modulation of NOTCH signaling receptor DLK1 [152].…”
Section: Microrna-101 129-5p and 193a-3pmentioning
confidence: 99%